2003
DOI: 10.1063/1.1585116
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of yttrium-stabilized HfO2 high-k gate dielectric thin films on Si

Abstract: Epitaxial yttrium-stabilized HfO 2 thin films were deposited on p-type ͑100͒ Si substrates by pulsed laser deposition at a relatively lower substrate temperature of 550°C. Transmission electron microscopy observation revealed a fixed orientation relationship between the epitaxial film and Si; that is, (100)Si//(100)HfO 2 and ͓001͔Si//͓001͔HfO 2 . The film/Si interface is not atomically flat, suggesting possible interfacial reaction and diffusion. X-ray photoelectron spectrum analysis also revealed the interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…3 show the C-V behavior of a typical MOS device, with three distinct regimes of accumulation, inversion and depletion. A relative dielectric constant (K) of about 13.5 was obtained from the MOS structure with 65 nm HfO 2 film, which is comparable with the previous results obtained with HfO 2 films prepared by more complex techniques, e.g., K = 14 by pulsed laser deposition (PLD) [8], K = 10-12 by atomic layer deposition (ALD) [9], and K = 10-11 by ALD [10].…”
Section: Resultssupporting
confidence: 63%
“…3 show the C-V behavior of a typical MOS device, with three distinct regimes of accumulation, inversion and depletion. A relative dielectric constant (K) of about 13.5 was obtained from the MOS structure with 65 nm HfO 2 film, which is comparable with the previous results obtained with HfO 2 films prepared by more complex techniques, e.g., K = 14 by pulsed laser deposition (PLD) [8], K = 10-12 by atomic layer deposition (ALD) [9], and K = 10-11 by ALD [10].…”
Section: Resultssupporting
confidence: 63%
“…23 The formation of SiO 2 seems to be dependent on the deposition process as observed in the ALD technique, where there is a distinct peak appearing at $103 eV. 24,25 The C-V measurements, as shown in Fig. 4, were carried out for the MIS devices in a frequency range of 10-400 MHz.…”
Section: Methodsmentioning
confidence: 99%
“…[24] Figure 4 demonstrates the core-level spectra of Hf 4f, and all of them are deconvoluted into two peaks of Hf 4f 5/2 and Hf 4f 7/2 , which are in accordance with spin-orbit splitting energy of about 1.7 eV. [25][26][27] From the above XPS results, it can be suggested that the HfGdON dielectric film is formed. By calculating the peak-area ratio of Gd 4d to Hf 4f for each of the three Gd-doped samples, their Gd content values [Gd/(Gd+Hf)] are obtained to be 13.16%, 29.86%, and 45.47%, respectively.…”
Section: Resultsmentioning
confidence: 78%